EVALUASI KEHUMASAN DI UNIVERSITAS UDAYANA - Prabasari, Ni Luh Putu Galuh; Purnawan, Ni Luh Ramaswati; Sugiarica Joni, I Dewa Ayu (E-Jurnal Medium, 2017)
ABSTRACT PR today face different challenges from the past not just matter of financial support and internal management, but also the explosive issue, such as opposition to the policy new admissions, crisis or students drug crimes, sexual harassment, and much more. Considering the complexity that must be faced by a college, it’s necessary to optimize the role of public relations in college. This research explains how PR is managed, especially in Udayana University, which focused on three aspects, institutional, public relations activities, and human resources. Through the analysis is that the information obtained from the analysis of the situation and the issues separating the internal (strength and weaknesses and external subject matter (opportunities and threats) and create strategies to deal with it. This study, showing institutional public relations at the Udayana University not well organized yet. Its position was far from the decision-makers. Although publicist finally listed in the new OTK, but the duties and functions of public relations remains unclear. The position is also unchanged, as it still is in the management level but with different bosses. Public relations tasks at Udayana University were communication technician (technical officer). So does with human resource in it that does not have a background in public relations and minimal training. The position of the institutions that perform public relations function need to be separate from law and governance into a special bureau and are close to the leadership. PR should be more creative and innovative in making programs that can help accelerate of Objectives University. PR needs to be improved quality of human resource through training. Key words: Evaluation, Public Relations, SWOT Analysis